ETUDE DE L’ISOTHERME 25 °C DU SYSTEME QUASI QUATERNAIRE H2O - Zn(NO3)2,6H2O – Cu(NO3)2,3H2O - NH4NO3 II- ISOPLETHES : 41 MASSE % Cu(NO3)2, [MASSE DE NH4NO3] = -10/9 [MASSE DE Zn(NO3)2] + 100, [MASSE DE H2O] = 0.5702 [MASSE DE ZN(NO3)2] + 0.2879[ MASSE DE (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The solid-liquid equilibria of the quasi quaternary system H2O Zn(NO3)2,6H2O Cu(NO3)2,3H2O-NH4NO3 were studied at 25°C by using a synthetic method based on conductivity measurements. Three isoplethic sections has been established at 25°C and the stable solid phases which appear are: NH4NO3 (IV), Zn(NO3)2,6H2O, Cu(NO3)2,3H2O and metastable Cu(NO3),2.5H2O. Neither double salts, nor mixed crystals are observed at these temperature and composition range.